A COURSE TO THE SOCIAL CLASS CATEGORY OPERATIONALIZATION IN A GEOGRAPHY RESSEARCH - Dias, Patrícia Chame (GeoTextos, 2021)
Based on Marxist understanding regarding capitalism and supposing that one’s position on the social structure influences their possibilities of space usage and appropriation, I have developed a doctorate thesis in which, among other aspects, I have proposed some criteria to operationalize the social class category. This text is a result of this paper’s reevaluation, therefore intend to reflect on such criteria, based on a Geography research experience. To achieve that, I present a synthesis of the theoretical course which led to the adopted procedures, expose such procedures, and analyze adopting criteria related to one’s occupation as well as their trajectory in order to understand their class. This discussion is made mainly based on the field findings and the linking between theory and practice. I also mark the possibility of taking their world interpretations and their practices in consideration as an element that indicates their position on the social structure.